2002
DOI: 10.1074/jbc.m112087200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Metallation and Activity in Subsets of Mutant Superoxide Dismutases Associated with Familial Amyotrophic Lateral Sclerosis

Abstract: Over 90 different mutations in the gene encoding copper/zinc superoxide dismutase (SOD1) cause ϳ2% of amyotrophic lateral sclerosis (ALS) cases by an unknown mechanism. We engineered 14 different human ALSrelated SOD1 mutants and obtained high yields of biologically metallated proteins from an Sf21 insect cell expression system. Both the wild type and mutant "as isolated" SOD1 variants were deficient in copper and were heterogeneous by native gel electrophoresis. By contrast, although three mutant SOD1s with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
350
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(376 citation statements)
references
References 54 publications
(46 reference statements)
19
350
0
Order By: Relevance
“…Transgenic mice overexpressing either WT SOD1 (line B6SJL-TgN(SOD1)2Gur) or G93A SOD1 (line B6SJL-TgN(SOD1-G93A)1Gur) (4) were obtained from the Jackson Laboratory (Bar Harbor, ME), whereas those overexpressing G85R SOD1 (7) bred to homozygosity were provided by Dr. Zuoshang Xu. WT or ALS-related mutant SOD1 enzymes (A4V, L38V, G41S, H46R, H48Q, G72S, D76Y, G85R, D90A, G93A, D124V, D125H, E133⌬, and S134N) containing biologically incorporated metal ions were isolated from a baculoviral expression system (18). Protein concentrations were estimated using a dimeric molar extinction coefficient at 280 nm of 10,800 M Ϫ1 cm Ϫ1 (32) or 13,800 M Ϫ1 cm Ϫ1 for D76Y SOD1 (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice overexpressing either WT SOD1 (line B6SJL-TgN(SOD1)2Gur) or G93A SOD1 (line B6SJL-TgN(SOD1-G93A)1Gur) (4) were obtained from the Jackson Laboratory (Bar Harbor, ME), whereas those overexpressing G85R SOD1 (7) bred to homozygosity were provided by Dr. Zuoshang Xu. WT or ALS-related mutant SOD1 enzymes (A4V, L38V, G41S, H46R, H48Q, G72S, D76Y, G85R, D90A, G93A, D124V, D125H, E133⌬, and S134N) containing biologically incorporated metal ions were isolated from a baculoviral expression system (18). Protein concentrations were estimated using a dimeric molar extinction coefficient at 280 nm of 10,800 M Ϫ1 cm Ϫ1 (32) or 13,800 M Ϫ1 cm Ϫ1 for D76Y SOD1 (33).…”
Section: Methodsmentioning
confidence: 99%
“…We previously purified 14 different biologically metallated ALS mutant SOD1s and observed that one group of "WT-like" mutants (A4V, L38V, G41S, G72S, D76Y, D90A, G93A, and E133⌬) bound copper in a fully active coordination environment remarkably similar to that of normal SOD1 despite causing a lethal phenotype (18). The other six "metal-binding region" mutants (H46R, H48Q, G85R, D124V, D125H, and S134N) were clearly distinguished from WT SOD1 according to decreased metal ion contents, altered visible absorption spectra, or decreased specific activities.…”
mentioning
confidence: 99%
“…Therefore, an impaired maturation process would lead to the accumulation of immature SOD1 species, which are prone to oligomerization. Recent studies reported a higher propensity for deficient protein maturation in vivo or in-cell culture models for some fALS mutants 39,40 . However, most of the studies addressing the properties of fALS SOD1 mutants and their effects on the maturation process have been performed in vitro, therefore, far from physiological conditions [41][42][43] .…”
mentioning
confidence: 99%
“…Three distinct bands of SOD1 activity are observed in samples from EGFP-SOD1 wt -and EGFP-SOD1 G93A -transfected cells, representing the dimers of endogenous untagged SOD1, EGFP-SOD1 dimers, and the respective heterodimers. In contrast to the 'wt-like' SOD1 G93A , in cells transfected with the dismutase-dead mtSOD1 G85R , 23 only endogenous SOD1 wt activity could be detected. CON: untransfected control cells.…”
Section: Resultsmentioning
confidence: 75%
“…In contrast to EGFP-SOD1 G93A , enzymatic activity was lost by EGFP-SOD1 G85R , as observed before for the untagged SOD1 G85R mutant. 23 The finding that our SOD1 fusion proteins still dimerize and -if not abolished by the respective mutation -exhibit normal dismutase activity, indicates that the EGFP tag does not preclude proper maturation, dimerization and copper loading of SOD1. This was further confirmed by the presence of the intramolecular disulfide bond in EGFP-SOD1 fusion proteins that is essential for activity and stability ( Figure 1c).…”
Section: Resultsmentioning
confidence: 84%